Enriching Banking Vocabulary in English for LPD Employees Using the Crossword Puzzle Method - Ni Luh Putu Unix Sumartini; I Gede Putu Adhitya Prayoga; Luh Putu Rika Utami (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
The crossword puzzle method is utilized to enhance English vocabulary proficiency among employees of a local financial agency named LPD (Lembaga Perkreditan Rakyat) which is located at Guwang Village, Gianyar Regency. This research adopts a qualitative approach combined with a case study model and a pre-experimental design to assess the method’s effectiveness. 15 employees with diverse educational backgrounds, ranging from high school (SMA), vocational school (SMK), diploma, to bachelor’s degree are participated in this research. This research applied crossword puzzle set as the instrument which contained of 20 English financial glossaries. The data collection was conducted through the distribution of questionnaires and preliminary interviews to assess the employees’ understanding of banking terminology in English before and after the training. Data analysis was performed using an interactive model that includes three main stages: data collection, data analysis, and conclusions. The results showed that the crossword puzzle method is fruitful in enhancing employees’ interest in actively learning English vocabulary. Furthermore, the method also expanding their confidence in using English, especially in the context of banking terminology. The evaluation results revealed that 4 employees (27%) only mastered fewer than 10 vocabulary items after the training (Category A), 5 employees (33%) mastered between 10 to 15 vocabulary items (Category B), and 6 employees (40%) successfully mastered more than 15 vocabulary items (Category C). These findings indicate a significant improvement in vocabulary mastery, although there are still differences in the level of proficiency among the participants. Overall, this method has a positive impact on employees’ English vocabulary mastery, particularly in banking terms, and has the potential to be applied more widely in other workplace settings.